Assessment of Acute and Chronic Toxicity in Wistar Rats (Rattus norvegicus) and New Zealand Rabbits (Oryctolagus cuniculus) of an Enriched Polyphenol Extract Obtained from Caesalpinia spinosa - Ricardo Ballesteros-Ramírez; Paola Lasso; Claudia Urueña; Jenny Saturno; Susana Fiorentino (Journal of Toxicology)
Although herbal drugs are often considered safe for consumption, there is increasing evidence that some can generate undesirable health effects. However, polyphenols found in certain plants have been shown to provide a range of benefits for human health. In previous work, a standardized and quantified extract (P2Et) obtained from Caesalpinia spinosa (Dividivi) plant showed promising antioxidant, immunomodulatory, and anti-inflammatory properties in animal models of cancer and COVID-19 patients. The extract has also been subjected to genotoxicity, mutagenicity, and 28-day oral chronic toxicity evaluations, demonstrating a good safety profile. To advance preclinical and clinical development, further acute and chronic toxicity evaluations of the P2Et extract were performed. Acute toxicity tests were performed orally in Wistar rats at a dose of 2000 mg/kg, indicating that the lethal dose 50% (LD50) value exceeded 2000 mg/kg and classifying the P2Et extract as category 5 according to the Globally Harmonized System of Classification (GHS). In this work, chronic toxicity tests were conducted for 180 days on Wistar rats and New Zealand rabbits at a dose of 1000 mg/kg under Good Laboratory Practice (GLP) conditions. No weight loss or alterations in biochemical and hematological parameters associated with treatment were observed in the animals, suggesting the absence of toxicity in the assessed parameters. These results indicate that the P2Et extract is safe for oral administration at doses up to 1000 mg/kg body weight over a six-month period.